Experimental Investigation on Size Effect in Shear of High-Strength Concrete Beams - Tavio (IPTEK The Journal for Technology and Science, 2025)
In this paper, an experimental program on the size effect in high-strength reinforced concrete beams is described. A total of 18 deep and slender specimens with effective depth d ranging from 200 to 700 mm and shear span a ranging from 400 to 2450 mm were tested to failure under two-point symmetric top loading. Test variables were shear span to effective depth ratio a/d, web reinforcement percentage and the effective depth d. The compressive cylinder strengths f1 c of the beams vary from 75 to 104 MPa. The beams had the main steel ratio of 3.98 percent. Test results reveal that the ultimate shear stress is size dependent. Besides the shear span to effective depth ratio a/d, the effective depth d also has a significant influence on the failure mode and the ultimate shear stress; larger deep beams are more brittle in comparison with smaller ones. The 18 test results are then compared with predictions from the current ACI Code, Zsutty’s equation, Bazant’s method, and Strutand- Tie model. Comparison study shows that while the safety of the ACI Code and Zsutty’s equation reduces for larger concrete beams, Bazant’s equation predicts well the trend on the influence of effective depth d in highstrength concrete beams. The Strut-and-Tie model can predict the trend on the influence of effective depth in high-strength concrete deep beams, but overestimates the shear capacities of the beams.